Recent Advances in Manifold Exfoliated Synthesis of Two‐Dimensional Non‐precious Metal‐Based Nanosheet Electrocatalysts for Water Splitting. Issue 1 (23rd November 2021) - Kou, Zhenhui; Wang, Kexin; Liu, Zhibin; Zeng, Libin; Li, Zhongjian; Yang, Bin; Lei, Lecheng; Yuan, Chris; Hou, Yang
Abstract : Electrochemical water splitting has been widely recognized as efficient technology to produce high‐purity hydrogen as environmental‐friendly fuels. The main challenge of electrochemical water splitting is in the development of low‐cost earth‐abundant electrocatalysts to enable their large‐scale applications in industry. Two‐dimensional (2D) materials have been developed as promising electrocatalysts due to their abundant exposed active sites, high surface area and fast transfer ability of electrons. However, currently, there is a lack of review work in literature elucidating the most recent advances on the research and development of 2D precious‐free electrocatalysts and their state‐of‐the‐art performances in water splitting. Herein, the authors present a review of recent progress of development on diverse exfoliation methods for synthesizing multi‐category 2D non‐precious metal‐based (NPMB) electrocatalysts to split water into hydrogen and oxygen. The leading methods are composed of guest ions or molecules‐assisted, auxiliary force‐assisted, electrochemical‐assisted exfoliation and additional exfoliation for fabricating these 2D NPMB nanosheets, including transition‐metal dichalcogenides, oxides, carbides, nitrides, layered double hydroxides, metal‐organic frameworks and mono‐elemental materials. The structure‐activity relationships of enhanced catalytic performance and downsizing nanostructure of corresponding 2D NPMB nanosheets are discussed. Finally, existent puzzle and prospective direction for designing synthesis methods of 2D NPMB electrocatalysts for water splitting are put forward. Abstract : Recent progress regarding diverse exfoliation synthesis of ultrathin 2D nonprecious metal‐based nanosheets with outstanding electrocatalytic activity for water splitting is reviewed, with corresponding structure–performance relationship highlighted.